Beyond Serum Creatinine: Urinary KIM-1 as a Predictive Biomarker for Subclinical Acute Kidney Injury and Chronic Kidney Disease Progression: A Systematic Review and Meta-Analysis - Puti Anggun Sari; Drajad Priyono (HM Publisher, 2026)
Background: The global burden of chronic kidney disease (CKD) is escalating, requiring earlier and more precise diagnostic modalities. Traditional reliance on serum creatinine and glomerular filtration rate (GFR) creates a significant blind spot regarding structural tubular integrity. A dangerous diagnostic window known as subclinical acute kidney injury (AKI) exists when tubular damage progresses despite preserved filtration function. This study aims to systematically analyze the diagnostic accuracy of urinary kidney injury molecule-1 (uKIM-1) in detecting subclinical injury and quantify its predictive value for CKD progression in populations where serum creatinine fails to provide an early warning. Methods: A systematic review and meta-analysis of five pivotal studies were conducted, encompassing experimental models of ischemia-reperfusion and human cohorts involving Autosomal Dominant Polycystic Kidney Disease (ADPKD), Diabetic Nephropathy, and Contrast-Induced AKI. Data were synthesized using random-effects models to calculate Standardized Mean Differences (SMD) and pooled Hazard Ratios (HR) to assess the prognostic value of uKIM-1 for long-term renal decline. Results: The analysis demonstrated that uKIM-1 levels remained significantly elevated during apparent functional recovery where serum creatinine had returned to baseline. In experimental models, persistent uKIM-1 elevation correlated strongly with histological evidence of interstitial fibrosis (r > 0.70). Clinical cohorts revealed that elevated KIM-1 is a robust independent predictor of progression to ESRD, with hazard ratios ranging from 1.34 to 3.30. Pooled analysis showed a Risk Ratio of 2.45 (95% CI: 1.55 – 3.88; p < 0.0001). Conclusion: Urinary KIM-1 serves as a sensitive and specific biomarker for subclinical tubular injury, identifying the at-risk